Effects of Tibolone on the Breast of Postmenopausal Women - Peng-Hui Wang; Ming-Huei Cheng; Hsiang-Tai Chao; Kuan-Chong Chao (Elsevier, 2007)
For decades, hormone therapy (HT) has been the mainstay for managing menopausal symptoms. However, the prolonged use of either single estrogen therapy (ET) or a combination therapy of estrogen and progestogen (EPT) might be associated with a slightly increased risk of breast cancer. Alternative therapies that are effective in the prevention and/or treatment of menopause, having associated morbidities but no unwanted effects, are of primary interest in clinical practice. Tibolone (Livial; NV Organon, Oss, The Netherlands) is structurally related to 19-nortestosterone derivatives and is a new postmenopausal regimen with a unique pharmacological profile, licensed for the relief of climacteric symptoms and the prevention of osteoporosis in postmenopausal women. Tibolone exhibits weak estrogenic, progestogenic, and androgenic activities, which in theory might influence the breast. The effect of tibolone on breast tissue, however, is obscure. The purpose of this study was to assess the effects of tibolone on breast safety, and the collected data include preclinical models, clinical observation, and epidemiologic study. Although in vitro studies showed conflicting results (with the majority being favorable effects) regarding the effects of tibolone on breast cells, in vivo studies showed favorable effects of tibolone on the breast in animal models. Similarly, an epidemiologic study indicated an increased risk of breast cancer when tibolone was used to manage climacteric symptoms of postmenopausal women, but accumulated data obtained from radiologic studies (mammography) showed a possible protective effect of tibolone on the breast. Taken together, we conclude that tibolone, if not superior to conventional HT, may be more acceptable to clinicians as a therapeutic drug option for use with symptomatic menopausal women. Only time will tell whether tibolone will be the preferred option.